عمل محطة طاقة حرارية شمسية ذات لاقط من نوع قطع مكافئ عند الحمولات الجزئية المتغيرة في مدينة تدمر - علي, محمد; أحمد, مها; حمادة, قمر (Latakia University Journal -Engineering Sciences Series, 2018)
Solar radiation which reaches the earth surface in Palmyra city has high rates, so we introduce this research to study the operation of a solar electric power plant with parabolic trough solar collector type. Electric power plants are usually designed to operate at nominal design power and flow rate, pressure, specific steam temperature. In this case the obtained efficiency is relatively high, but the real conditions in which the plant operates and supplies the electric grid, in addition to the climate variations during monthes and seasons, all lead to a deviation in power value from nominal value, so the plant operate at partial loads. We used the analytical method in this research to study the variation in power plant parameters as the steam turbine load changes. In other words, the study of main plant parameters variation due to variable partial loads. We calculated steam pressure variations through turbine stages and its effect on changing steam flow rate to the recovery water heaters. In addition, we calculated the amount of heat consumed through turbine unit, turbine unit efficiency, and the total efficiency of the power plant. تتميز منطقة تدمر بمعدلات عالية لكمية الإشعاع الشمسي الواصلة لسطح الأرض, لذلك قمنا في هذا البحث بدراسة عمل محطة حرارية كهروشمسية ذات لاقط من نوع قطع مكافئ. عادةً تصمم محطة توليد الطاقة الكهربائية لتعمل عند الاستطاعة الإسمية التصميمية وعند تدفق وضغط ودرجة حرارة بخار محددة بالتالي الحصول على مردود مرتفع نسبيا, غير أن الظروف الفعلية لتشغيل واستثمار المحطة الكهروشمسية ضمن الشبكة الكهربائية ومساهمتها في تغطية الطلب على الطاقة الكهربائية وتغير الظروف المناخية تبعا للشهور ولفصول السنة يؤدي إلى انحراف الاستطاعة المولدة عن ظروف العمل الاسمية وبالتالي إلى عمل المحطة عند حمولات جزئية. اعتمدنا في بحثنا على منهجية تحليلية لدراسة تغير بارمترات المحطة عند تغير حمولة العنفة البخارية, أي دراسة تغير المؤشرات الرئيسية للمحطة عند حمولات جزئية متغيرة. كما قمنا بحساب تغير ضغط البخار عبر مراحل العنفة وتأثيره على تغير تدفق البخار المتجه نحو مسخنات الماء الإسترجاعية كما قمنا بحساب كمية الحرارة المستهلكة في وحدة العنفة، وحساب مردود وحدة العنفة البخارية والمردود الإجمالي للمحطة.